Connotative Meanings in English Song Lyrics of Flying Solo Album by Pamungkas - Kurniawan, Deka Dwi; Netra, I Made; Rajeg, Gede Primahadi Wijaya (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
Song lyrics are literary works created by musicians to convey their ideas, feelings, and emotions. In making song lyrics, the writer is free to choose the words they will use to express their ideas or feelings and the meaning they want to convey. Generally, in making song lyrics, musicians use implied meanings so that the songs are more interesting to listen to. The phenomenon that often occurs is that there are still many people who misinterpret the meaning to be conveyed, especially the implied meaning (connotative meaning). Based on the phenomenon that often occurs, the purpose of this study is to find out the types of connotative meanings in song lyrics. The documentation method and note-taking technique were used in this study. The data source is taken from the song lyrics of Pamungkas' Flying Solo album. The song lyrics in the album are downloaded via the website. Then, understand the lyrics that have been downloaded while collecting the words or phrases that are thought to have connotative meaning. Furthermore, classifying and explaining messages from the data that has been collected. The data in this study were analyzed based on the theories of types of connotative meaning proposed by Hook and denotative and connotative meaning proposed by Leech. The result of this study shows that the song lyrics on this album contain three types of connotative meaning, which are positive, negative, and neutral connotative. Keywords: Song Lyric, Phenomena, Types of Connotative Meaning